SOLVING THE PROBLEM OF IMPROVING STUDENTS’ ATTENTION - Kodirov Ziyodulla Abdumukhtarovich (Ecomind Press, 2025)
Teaching a subject based on his or her own experience and specific technical problems is one of the most effective and interesting tools for science. In this regard, when teaching science, we must consider the following today: - as far as possible, based on familiar technical devices and life events; - Providing opportunities for the classroom to solve the current problems of the future profession and the application of life examples of this profession.
Keywords: Attention, historians, psychologists, concentration, special efforts, mental process, habit, value, attract, provocative, fatigue, activity, improvement, emotionality.